Case Report: DNAAF4 Variants Cause Primary Ciliary Dyskinesia and Infertility in Two Han Chinese Families - Guo, Ting; Lu, Chenyang; Yang, Danhui; Lei, Cheng; Liu, Ying; Xu, Yingjie; Yang, Binyi; Wang, Rongchun; Luo, Hong (Frontiers in Genetics, 2022)
Background Primary ciliary dyskinesia (PCD) is a rare genetic disorder that is predominantly autosomal recessive. Dynein Axonemal Assembly Factor 4 (DNAAF4) is mainly involved in the preassembly of cilia multi-subunit dynein protein. It is fundamental to the proper functioning of cilia and flagella. There are few reports of primary ciliary dyskinesia (PCD) related pathogenic variants of DNAAF4 and almost no DNAAF4-related articles focus on sperm phenotype. Moreover, the association between DNAAF4 and scoliosis has never been reported before. Materials and Methods We recruited two patients with a clinical diagnosis of PCD, one from a consanguineous family and the other from a non-consanguineous family. Through a comprehensive analysis of their clinical data, laboratory tests, imaging data, genetic sequencing information, immunofluorescence, electron microscopy images, high-speed video microscopy analysis and hematoxylin-eosin staining, we gradually identified the pathogenicity of the variants. Results Proband 1 (P1, F1: II-1), a 19-year-old male, comes from a non-consanguineous family-Ⅰ and proband 2 (P2, F2: II-1), a 37-year-female, comes from a consanguineous family-Ⅱ. Both of them had sinusitis, bronchiectasis, situs inversus and scoliosis. P1 also had asthenoteratozoospermia and P2 had immature uterus. Two pathogenic variants in DNAAF4, c.988C>T, p.(Arg330Trp) and c.733 C>T, p.(Arg245*) , were identified through genetic test. High-speed microscopy showing a few remnants of beating of respiratory cilia in P1, complete static of the respiratory cilia in P2. Immunofluorescence showed that the outer dynein arms (ODA) and inner dynein arms (IDA) were absent in the respiratory cilia of both probands as well as in the sperm flagellum of P1. Transmission electron microscopy (TEM) revealed the absence of ODA and IDA of respiratory cilia of P2. HE staining showed irregular, short, absent, coiled, and bent flagella. Conclusion: Our study identified a new variant c.733C>T, which expanded the spectrum of DNAAF4 variants. Furthermore, we linked DNAAF4 to asthenoteratozoospermia and likely scoliosis in patients with PCD. This study will contribute to genetic counselling for PCD.